Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms232416109
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Imaging of Inflammation, Fibrosis, and Cancer in the Gastrointestinal Tract

Abstract: Gastrointestinal disease is prevalent and broad, manifesting itself in a variety of ways, including inflammation, fibrosis, infection, and cancer. However, historically, diagnostic technologies have exhibited limitations, especially with regard to diagnostic uncertainty. Despite development of newly emerging technologies such as optoacoustic imaging, many recent advancements have focused on improving upon pre-existing modalities such as ultrasound, computed tomography, magnetic resonance imaging, and endoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 151 publications
(185 reference statements)
0
2
0
Order By: Relevance
“…Further, given the link between hypoxia and tumor response to radiation therapy, oxygen-sensitive MRI could also assist in response monitoring and outcome prediction during radiation therapy [62] . Similarly, oxygen-enhanced MSOT (OE-MSOT) and other hypoxia-sensitive MSOT techniques [37] , [63] , [64] demonstrated comparable capabilities to monitor tumor oxygenation in real-time, and the unique strengths of MSOT, including portability, high spatiotemporal resolution, etc., potentiates its application in certain clinical settings infeasible for MRI and other imaging modalities. It should, however, be noted that the labeling of 2-DG with IRDye800 alters the metabolism of 2-DG and may not dynamically reflect glucose metabolism, in contrast to MRI technologies that require no labeling for dynamic imaging, e.g., chemical exchange saturation transfer (CEST) MRI [65] .…”
Section: Discussionmentioning
confidence: 99%
“…Further, given the link between hypoxia and tumor response to radiation therapy, oxygen-sensitive MRI could also assist in response monitoring and outcome prediction during radiation therapy [62] . Similarly, oxygen-enhanced MSOT (OE-MSOT) and other hypoxia-sensitive MSOT techniques [37] , [63] , [64] demonstrated comparable capabilities to monitor tumor oxygenation in real-time, and the unique strengths of MSOT, including portability, high spatiotemporal resolution, etc., potentiates its application in certain clinical settings infeasible for MRI and other imaging modalities. It should, however, be noted that the labeling of 2-DG with IRDye800 alters the metabolism of 2-DG and may not dynamically reflect glucose metabolism, in contrast to MRI technologies that require no labeling for dynamic imaging, e.g., chemical exchange saturation transfer (CEST) MRI [65] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it plays a crucial role in guiding the modification and implementation of treatment strategies for intestinal diseases [49,50]. The endoscopic results demonstrated that Pt NP treatment significantly reduced colon mucosal congestion, edema, and ulceration in the UC mouse model (Figure 6I).…”
Section: Protective Effect Of Pt Nps Against Colitismentioning
confidence: 97%
“…Furthermore, it makes use of oral contrast agents to visualize the extent of bowel wall abnormalities and evaluate inflammatory activities [ 65 , 70 ]. Recent development in the field of artificial intelligence has allowed for the realization of CT-based deep learning models which have proven to outperform human interpreters with increased accuracy and objectivity [ 73 ]. This technology’s main limitation, however, is that of exposure to ionizing radiation [ 65 , 68 ].…”
Section: Intestinal Fibrosismentioning
confidence: 99%